Bio-Priming of Seed with Trichoderma sp. and Bacillus sp. Leads to Improved Morpho-Physiological Parameters Related to Drought Tolerance in Maize - Iqbal, Aliza; Arshad, Usman; Ayub, Sabahat; Jabeen, Ayesha; Saeed, Muhammad (Integrative Plant Biotechnology, 2023)
Maize (Zea mays L.) holds an important position as a major grain crop in Pakistan flourishing across a diverse range of environmental conditions. The maize crop encounters various severe abiotic challenges with drought being the most concerning factor leading to diminished plant growth and yield. Seed priming a well-established and widely adopted technique serves as an effective mechanism to alleviate drought stress ultimately boosting both growth and grain yield. The primary objective of this study was to evaluate the impact of diverse seed priming methods on the growth and development of maize plants. Additionally, the study sought to assess the potential of various seed priming techniques in mitigating drought stress in maize. A pot experiment was conducted using a completely randomized design under natural conditions. The aim was to scrutinize the influence of different priming agents on morpho-physiological traits associated with water deficit conditions in maize. The gathered data underwent ANOVA analysis revealing variations in all parameters for both maize varieties at a 5% probability level. Specifically, the Pak-Afgoi variety displayed notable responsiveness to the seed priming approach in alleviating drought stress in maize. Furthermore, the findings underscored the evident and substantial impact of seed priming on both maize varieties across a range of studied characteristics under drought stress conditions. In conclusion, the present study suggests that seed priming holds the potential to enhance drought tolerance in maize.
Keywords: Maize; seed priming; drought tolerance; Trichoderma sp.; Bacillus sp.